FAKTOR YANG BERHUBUNGAN DENGAN PERKAWINAN USIA MUDA PADA PENDUDUK KELOMPOK UMUR 12-19 TAHUN DI DESA PUJI MULYO KECAMATAN SUNGGAL KABUPATEN DELI SERDANG TAHUN 2013 - Priyanti Anti; Maya Fitria; Erna Mutiara (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
ABSTRACT Young age marriage is a marriage conducted under the age of 20 years. Maturation age of marriage is an attempt to increase the age at first marriage, so it achieves the minimum age at marriage that is 20 years for women and 25 years for men. This study aimed to understand the factors related to early marriage of the population of the age group 12-19 years at the Puji Mulyo Village, Sunggal Subdistrict, Deli Serdang District in 2013. The study design was cross-sectional. The study population was the entire population of the age group 12-19 years in 2012 as many as 1458 people. Sample is the population of the age group 12-19 years who had father and mother, had been dated, had a girl or boy friend. Data collection was done by using questionnaires. Data analysis was done by univariate and bivariate analysis using chi-square test. The results showed that of 81 population of the age group 12-19 years there were 22 people (27.2%) who did young age marriage. Also it was found no relationship between knowledge (p = 0.001), promiscuity (p = 0.001) and young age marriage. While there is no relationship between education (p = 0.325), father's education (p = 0.428), mother’s education (p = 0.545), culture (p = 0.060) and young age marriage. The village goverment is expected to cooperate with the school and the Office of Religious Affairs to provide counseling related to young age marriage on adolescent and to activate PIK-KRR (Center for Adolescent Reproductive Health Counseling Information) as a mean to obtain information about adolescent reproductive health especially about the meaning and impact of early marriage, the ideal age for marriage and marriage laws as well as parents should pay more attention to the development of their children and adolescents are more selective in choosing friends not to be involved in promiscuity. Keywords : Marriage, Young Age, Population Age 12-19 Years